Community radio advocacy in democratic Nigeria: lessons for theory and practice (2009)
"This article describes the challenges of working toward an enabling policy and legal environment for community radio in Nigeria. Given the acute development problems it faced and years of autocracy, expectations were that when Nigeria became a democracy, it would immediately deploy all tools, including community radio, to enhance development and participation. Theorists suggest that democracy should be accompanied by enlarged opportunities for expression occasioned by, among others, the removal of the restraints imposed on media ownership by autocrats. But ten years into democracy, Nigeria has yet to allow the establishment of community radio stations. The article identifies five phases of the advocacy for community radio and how it has reached a deadlock. Enlarging the opportunities for expression, in this case through licensing community radio stations, has proved to be as difficult in Nigeria during democracy as it was in the military period. This has lessons and challenges for theory and advocacy. "